Ethics briefings - English, Veronica (Journal of medical ethics, 2005)
In April 2005, the House of Lords Select Committee on the Assisted Dying for the Terminally Ill Bill published its findings.1,2,3 The committee’s remit had been to consider whether the second bill on “assisted dying” introduced by Lord Joffe in March 2004 should proceed, fall or be amended. Since it was clear, however, that the bill could not progress in that parliamentary session because of shortage of time, the committee chose to report on the evidence it had received rather than rule on the acceptability or otherwise of the bill. Volume two set out the evidence and volume one gave the committee’s views on the testimony received, including information about Holland, Switzerland, Belgium, and Oregon where either euthanasia, assisted suicide or both are already legal. Sixty organisations submitted evidence to the committee. Among these were organisations representing UK health professionals. In an earlier Ethics briefing,4 we drew attention to the disparity of views expressed. At that point, the British Medical Association (BMA) had firm policy opposing the legalisation of all forms of assisted dying (both euthanasia and assisted suicide). The Royal Colleges of General Practitioners (RCGP) and Physicians (RCP) had dropped their objections to the Assisted Dying Bill. This caused one of the committee members, Baroness Jay, to confess that she found herself confused by the profession’s position. She argued that it would be “more sensible, more professionally legitimate” for the BMA and General Medical Council (GMC) to take a “studiedly neutral position” as the colleges had done (House of Lords, 2 p 118, q 300). To add to the confusion the position of the BMA and that of the RCGP subsequently changed. After discussion, the RCGP decided that it would not continue to adopt a neutral position on assisted dying but did not agree …